CLOUD COMPUTING SEBAGAI STRATEGI OPTIMASI PERLUASAN TARGET PASAR USAHA KECIL MENENGAH DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Muhammad Imam Ghozali; Wibowo Harry Sugiharto; Zaenal Afifi (Jurnal Mantik Penusa)
Industry 4.0 requires each industry to be involved in the global market (international market), which involves all places in the world, and not limited to one country. Global marketing accepts the existence of complex (geocentric) world market similarities through the integration of dosmetic, foreign and international marketing activities. So the scope of marketing targets is greater than a traditional market. To be able to help a local UKM to face the global market in the industrial revolution 4.0, can utilize technology from cloud computing which is a technology that makes the internet as a center for data management and applications. From the results of this study the service on cloud computing that best suits the needs of UKM in conducting global marketing is IaaS.